Efeito da privação e restrição de sono na função reprodutiva de ratos machos - Alvarenga, Tathiana Aparecida Fernandes [UNIFESP] (2011)
It has been reported that copulatory experience may actually alter sexual performance in male rats. But indicating experience is a risky proposition since the statement is made in the absence of an established hormonal basis and number of copulations that define sexual experience condition. And also, the associated hormonal alterations observed in sexually high performing rats could have been caused by factors other than experience, such as sleep deprivation (SD). Whether it is trading sleep time for leisure time or for work, the shortage of sleep in present day society may lead to adverse alterations in body functions, even in the endocrine system, prompting changes sexual behavior and therefore, in reproductive function. In light of such considerations the current stage of the overall investigation forks into 2 studies: Study 1 seeks to determine the required time for the rat to acquire sexual experience as well as the hormonal profile of sexually active and sexually naïve rats. Study 2 examines the influence of sleep shortage upon sexual behavior (SB), hormonal profile, and spermatic parameters in sexually experienced rats. In Study 1 male rats underwent SB training in the presence of receptive females every other day over a nineday period. Results show that throughout this period 42.5% of the subjects displayed excellent sexual performance, 17.5% had adequate performance, 7.5% had low sexual activity and an unexpected 32.5% showed no sexual response at all. The hormonal analysis that followed showed that, when compared to subjects with adequate/excellent performance, the progesterone concentrations in the rats whose sexual performance was low or nil were decreased, as were those of testosterone. In Study 2 sexually experienced subjects underwent to a PSD protocol for 96h (PSD96h) and a sleep restriction protocol for 21 consecutive days (SR21d). In the latter, subjects experienced 18h of sleep deprivation followed by 6h in their home cages. Control groups (CTRL) remained in their home cages throughout the entire protocol. SB, hormonal profile and sperm analysis were assessed and it was found that PSD96h reduced sexual performance but SR21d did not alter SB in the rat subjects when compared to CTRL. As for hormonal alterations, the subjects submitted to PSD96h experienced a reduction in their levels of testosterone but no alterations occurred in the concentrations of progesterone, LH, and FSH. As for the semen analysis, both groups (PSD96h and SR21d), presented lower spermatic viability in relation to the CTRL. However, the loss of live spermatozoids was more pronounced in the PSD96h group than in the SR21d group. Taken together, the findings herein indicate that in addition to testosterone, progesterone is also a limiting factor in the sexual performance of male rats. And furthermore, that when submitted to PSD96h, rat subjects with excellent sexual activity loose sexual performance and also, they experience loss of spermatic viability as well as suffer decreases in testosterone concentrations. Likewise, there were also detrimental effects in the percentage of live spermatozoids in the SR21d subjects. The current study thus indicates that in order to maintain adequate sexual response an ideal concentration of not only testosterone but of the typically female hormone progesterone is also required. And also, regardless of the concentrations of one or another hormone involved in the cascade of events leading to spermatozoid formation, lack of sleep can be singled out as a detrimental factor in the reproductive function of male rats.